Opioid glycopeptide analgesics derived from endogenous enkephalins and endorphins. (February 2012) - Li, Yingxue; Lefever, Mark R; Muthu, Dhanasekaran; Bidlack, Jean M; Bilsky, Edward J; Polt, Robin
Over the past two decades, potent and selective analgesics have been developed from endogenous opioid peptides. Glycosylation provides an important means of modulating interaction with biological membranes, which greatly affects the pharmacodynamics and pharmacokinetics of the resulting glycopeptide analogues. Furthermore, manipulation of the membrane affinity allows penetration of cellular barriers that block efficient drug distribution, including the blood–brain barrier. Extremely potent and selective opiate agonists have been developed from endogenous peptides, some of which show great promise as drug candidates.